Enhancing power conversion efficiency of multicrystalline silicon solar cells by plasmonic effect of Ag nanoparticles embedded in SiNx layer - Ting Wang (AIP Advances, 2019)
In this paper, we demonstrate that the performance of the industrial multicrystalline silicon solar cells can be improved by embedding the silver nanoparticles (Ag-NPs) into the SiNx layer. On the one hand, the cells have a certain optical loss in short wavelengths near the plasmonic resonance frequency of Ag-NPs, but their open circuit voltages and filling factors are increased due to depressed surface recombination as those short wavelength photons are mainly absorbed by Ag-NPs instead of the surface; on the other hand, the cells show strong absorption in long wavelengths, which can be attributed to the forward-scattering effect of Ag-NPs. Taking together, UV-absorbing Ag-NPs may act as a “sunscreen” to shield the UV damage, while improve the cell efficiency from 18.05 % to 18.25 % by embedding proper Ag-NPs. The techniques presented in this work can be easily incorporated into the current mc-Si solar cell production line, thus have great potential for the mass practical application.